1981
DOI: 10.1038/ki.1981.152
|View full text |Cite
|
Sign up to set email alerts
|

Hyperosmolality, acetate, and lactate: Dilatory factors during peritoneal dialysis

Abstract: Factors that alter peritoneal blood flow may influence the clearance of solutes during peritoneal dialysis. Arteriolar vasodilation, for instance, could increase the delivery of solutes to the capillaries and venules leading to an increase in solute transport into the peritoneal cavity. This study was designed to identify the vasoactive effects of several major components of McGaw and Dianeal peritoneal dialysis solutions to understand how the composition of these solutions may alter in vivo blood flow in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
1
1

Year Published

1991
1991
2009
2009

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 14 publications
2
44
1
1
Order By: Relevance
“…These factors are well-known vasodilators, expected to increase the 'effective' capillary exchange surface area early during the dwell [13]. The effects of PD fluid lactate and hyperosmolality on the microvasculature have been studied previously by Miller et al [14]. These authors found that the factors mentioned, especially lactate, indeed, acted as vasodilators.…”
Section: Discussionmentioning
confidence: 79%
“…These factors are well-known vasodilators, expected to increase the 'effective' capillary exchange surface area early during the dwell [13]. The effects of PD fluid lactate and hyperosmolality on the microvasculature have been studied previously by Miller et al [14]. These authors found that the factors mentioned, especially lactate, indeed, acted as vasodilators.…”
Section: Discussionmentioning
confidence: 79%
“…However, it seems that the magnitude of such reactivity is modified by the H ϩ concentration, ionic contents, and other vasoactive components of the solution such as lactate, as well as by the specific solute metabolic activity. Indeed, earlier intravital videomicroscopy studies of the rat's cremaster muscle have shown that the magnitude of arteriolar dilation evoked by hyperosmolar solutions of dextrose, sucrose, or sodium chloride was similar but that the dilation rate constant differs among the three hyperosmolar solutions (2). Other perfusion studies of the dog's forelimb (28) and cat's ileum (29) have found that both the magnitude and the time course of the dilatory effects of hyperosmolar dextrose and sodium chloride solutions differed significantly.…”
Section: Vascular Reactivitymentioning
confidence: 99%
“…C onventional peritoneal dialysis solutions (PDS) dilate visceral and parietal microvasculature by mechanisms possibly related to hyperosmolality, low pH, and the buffer anion system of these solutions (1,2). Studies of hyperosmolar sodium solutions perfused into the intestinal lymph produced vasodilation of submucosal arterioles through a mechanism partially mediated by a hyperosmolality-induced nitric oxide (NO) release (3).…”
mentioning
confidence: 99%
“…Conventional PD fluids possess vasoactive properties [70][71][72][73]. The causative mechanisms as well as the pathophysiologic consequences of this PD fluid-induced vasodilatation, in particular the potential acute effects on fluid and solute transport and long-term changes of peritoneal function and structure, are incompletely understood.…”
Section: Glucose Degradation Productsmentioning
confidence: 99%